The Effect of Stroke Subtypes on Baroreceptor Sensitivity, a Predict for Acute Stroke Outcome. (18th April 2019) - Tsai, Wan-Chen; Lin, Hui-Chen; Lai, Yun-Ru; Hsu, Che-Wei; Huang, Chih-Cheng; Wang, Hung-Chen; Su, Chih-Min; Su, Yu-Jih; Lin, Wei-Che; Cheng, Ben-Chung; Chang, Wen-Neng; Lu, Cheng-Hsien; et al.
Abstract : Background . Reduced baroreflex sensitivity (BRS) has been reported in patients with acute cardiovascular events. We tested the hypothesis that BRS varies in different subtypes of acute ischemic stroke (AIS) and that BRS is a predictor of clinical outcomes. Methods . We examined autonomic parameters in 34 patients with AIS, including the small deep hemisphere infarction, the large hemisphere infarction, and the brainstem infarction groups on Day 1, Day 7, and Day 30 after AIS. Autonomic parameters were also evaluated in 18 age- and sex-matched healthy volunteers as a control group. The clinical outcomes were analyzed using the modified Rankin scale at 30 days after stroke. Results . The BRS, Valsalva ratio, and heart rate response to deep breathing (HR-DB) were significantly lower in patients after AIS on admission than in controls ( p <0.01). The frequency domain of HRV (LF/HF ratio) was significantly increased in patients after AIS compared to controls ( p <0.05). BRS was significantly reduced in patients with large hemisphere infarction or brainstem infarction compared to patients with small deep hemisphere infarction on Day 1 after AIS ( p <0.01). Stepwise logistic regression showed that the levels of BRS and NIHSS are prognostic factors of 1-month outcomes in patients with AIS. Conclusion . Beside NIHSS score on admission, BRS is a potential prognostic factor of 1-month outcomes in patients with AIS. Patients with large hemisphere infarction or brainstem infarction have more blunting BRS than do those with lacunar infarction, which provides some insight into which patients may be expected to have a poor outcome.